2016
DOI: 10.1002/jso.24190
|View full text |Cite
|
Sign up to set email alerts
|

The value of FDG‐PET in the staging of gastric adenocarcinoma: A single institution retrospective review

Abstract: Our findings support the use of FDG-PET as a valuable adjunct to CT in the staging of GA, as it changed the stage in 48 (28.9%) patients. J. Surg. Oncol. 2016;113:640-646. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…This guides treatment strategies away from the morbidity and mortality associated with a futile surgery, with no benefit for long-term survival, and avoidance of the considerable associated cost. This is consistent with previous studies, which have reported added information regarding occult metastases in up to 10% of patients [11,15,22,23]. A possible reason for the higher detection rate of metastases in our study compared to previous reports include improved scanning technology (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This guides treatment strategies away from the morbidity and mortality associated with a futile surgery, with no benefit for long-term survival, and avoidance of the considerable associated cost. This is consistent with previous studies, which have reported added information regarding occult metastases in up to 10% of patients [11,15,22,23]. A possible reason for the higher detection rate of metastases in our study compared to previous reports include improved scanning technology (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…As FDG PET-CT has become more routinely available, more studies have examined its role in the staging of gastric adenocarcinoma. Recent reports have estimated the added diagnostic value of FDG PET-CT for detecting occult metastases as 6-10% [11,15,22,23] with accompanying reductions in surgical morbidity, mortality and cost by the avoidance of unnecessary gastrectomy. Due to relatively low spatial resolution, FDG PET-CT does not add to assessment of primary tumour (T) stage [24].…”
Section: Introductionmentioning
confidence: 99%
“…PET-CT was also used in the preoperative judgement of lymph node metastasis and demonstrated its advantage on distant lymph node metastasis and bone metastasis [21]. However, the accuracy of PET-CT for regional lymph node metastasis did not demonstrate an advantage over CT or EUS [22]. In addition, it is not commonly accepted because of its radiation and expensive cost.…”
Section: Discussionmentioning
confidence: 99%
“…In Luo's study, for example, the results showed that the evaluation accuracy of pathological stages T1 and T2 for gastric cancer by spiral CT was approximately 42.86%. In general, the accuracy rates in recent studies using multi-detector row CT for T and N staging have been reported to be 71.4–88.9% and 64–78%, respectively [22–25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT has some limitations for predicting LN metastases before surgery (8). On the other hand, 18-fluorodeoxyglucose (FDG) positron emission tomography integrated with CT (PET-CT) is used to investigate LN metastases of non-GCs because of its high specificity (9,10). The predictive value of PET/CT for LN evaluation is dependent on the ability of primary tumors to uptake 18-FDG, the number of LN metastases, the size of the LNs, and the presence of inflammation in areas of the body.…”
Section: Introductionmentioning
confidence: 99%